2005
DOI: 10.1001/archinte.165.14.1600
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oral Topiramate to Promote Smoking Abstinence Among Alcohol-Dependent Smokers

Abstract: In this trial, topiramate (up to 300 mg/d) showed potential as a safe and promising medication for the treatment of cigarette smoking in alcohol-dependent individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
4
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 30 publications
2
97
4
1
Order By: Relevance
“…Topiramate, a sulfamate-substituted fructopyranose derivative, has been shown to be efficacious in the treatment of both alcohol (Johnson et al, 2003) and cocaine (Kampman et al, 2004) dependence, and to promote smoking cessation among alcohol-dependent individuals who smoke (Johnson et al, 2005a). These therapeutic effects have been attributed to its hypothesized potential to reduce levels of cortico-mesolimbic dopamine, the primary neurochemical substrate for the acquisition and maintenance of drug-seeking behavior for the majority of abused drugs including alcohol, cocaine, tobacco, and amphetamines (Hemby et al, 1997;Wise, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Topiramate, a sulfamate-substituted fructopyranose derivative, has been shown to be efficacious in the treatment of both alcohol (Johnson et al, 2003) and cocaine (Kampman et al, 2004) dependence, and to promote smoking cessation among alcohol-dependent individuals who smoke (Johnson et al, 2005a). These therapeutic effects have been attributed to its hypothesized potential to reduce levels of cortico-mesolimbic dopamine, the primary neurochemical substrate for the acquisition and maintenance of drug-seeking behavior for the majority of abused drugs including alcohol, cocaine, tobacco, and amphetamines (Hemby et al, 1997;Wise, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…9 Initially, complex epilepsy was the only indication for treatment with topiramate. Recently it has been suggested that topiramate may be useful in the treatment of obesity [10][11][12][13][14][15] , eating disorders [16][17][18][19][20] , migraine [21][22][23][24][25][26][27][28][29][30][31] , bipolar disorders [32][33][34][35] , other psychiatric disorders [36][37][38][39][40][41][42] , alcohol dependence [43][44][45][46][47] and other addictive disorders 48 . Also the drug is more frequently used in the management of childhood epilepsy [49][50][51] .…”
Section: Introductionmentioning
confidence: 99%
“…Topiramate-treated subjects were more likely to be abstinent from cocaine compared to placebo-treated subjects (Kampman et al, 2004), suggesting that topiramate may be effective for the treatment of cocaine dependence. In another clinical trial examining the effects of topiramate in alcohol dependent subjects, those assigned to topiramate were more likely to quit smoking than those assigned to placebo (19.4 vs 6.9% at week 12) (Johnson et al, 2005). These preliminary findings concerning the potential use of topiramate for the treatment of cocaine and nicotine dependence are encouraging.…”
Section: Introductionmentioning
confidence: 89%